(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
In the body of people from 18 to 50 years old 61% of body weight is water. In women, obese people and the elderly, this indicator is slightly lower. 70% of the water in the human body is cell protoplasm, 23% it forms interstitial fluid, and the remaining 7% forms blood plasma. A 10% reduction of water in the body puts a person in a difficult situation, and a 20-25% reduction kills a person. Water is especially abundant in the bodies of aquatic animals. For example, it makes up 99.7% of the body weight in jellyfish. In this article, we will discuss the incomparable role of water in our life, its conservation and proper distribution.